2016
DOI: 10.1080/13102818.2016.1202779
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Fusarium solani lipase in Pichia pastoris and its application in lipid degradation

Abstract: Fusarium solani NAN103 lipase was successfully overexpressed in Pichia pastoris using inducible expression system and constitutive expression system under the control of alcohol oxidase 1 promoter (pAOX1) and glyceraldehyde-3-phosphate dehydrogenase promoter (pGAP), respectively. Lipase obtained using the constitutive promoter showed the highest activity of 18.8 U/mg in 3 days of cultivation time. Optimal lipase activity was observed at pH 7.0 and 35 C using pnitrophenyl laurate as the substrate. Lipase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The developed method was also successfully applied to unconcentrated crude microbial culture media. We were able to detect lipolytic enzymes produced by Aspergillus aculeatus [ 29 ], Colletotrichum gloeosporioides [ 30 , 31 , 32 ], Fusarium solani [ 33 , 34 , 35 , 36 , 37 , 38 ], Penicillium expansum [ 6 , 39 , 40 , 41 , 42 ], and Trichoderma harzianum [ 43 , 44 , 45 , 46 , 47 ]. The choice of substrates used in chromogenic agar detection is not limited to triglycerides, but could also extended to di- or monoglycerides, vinyl laurate and other acyl ester substrates, which would be beneficial for screening of partial-glyceride lipases or steryl esterases.…”
Section: Discussionmentioning
confidence: 99%
“…The developed method was also successfully applied to unconcentrated crude microbial culture media. We were able to detect lipolytic enzymes produced by Aspergillus aculeatus [ 29 ], Colletotrichum gloeosporioides [ 30 , 31 , 32 ], Fusarium solani [ 33 , 34 , 35 , 36 , 37 , 38 ], Penicillium expansum [ 6 , 39 , 40 , 41 , 42 ], and Trichoderma harzianum [ 43 , 44 , 45 , 46 , 47 ]. The choice of substrates used in chromogenic agar detection is not limited to triglycerides, but could also extended to di- or monoglycerides, vinyl laurate and other acyl ester substrates, which would be beneficial for screening of partial-glyceride lipases or steryl esterases.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is a strong constitutive promoter, no induction step is required, resulting in simpler and shorter fermentation cultivations. The expression of Fusarium solani NAN103 lipase (FSL) under pGAP or pAOX1 showed that pGAP-FSL produced the highest specific lipase activity and, in addition, there was a two-day reduction in the cultivation time [88]. Many promoters with different strengths and properties are available for expression in K. phaffii.…”
Section: Eukaryotic Expression Systemsmentioning
confidence: 99%
“…The accumulation of lipid in the cells occurs via a dynamic equilibrium of fatty acid synthesis and degradation [31]. When degraded by lipases, TAGs are hydrolyzed into free fatty acids and glycerol [32]. Production of glycerol during the course of fungal cultivation in CWFS has probably been performed though a similar mechanism.…”
Section: Production Of Fungal Biomass For Incorporation Into Pectin Fmentioning
confidence: 99%